Clear cell ovarian cancer and endometriosis: is there a relationship? - Szubert, Maria; Suzin, Jacek; Obirek, Katarzyna; Sochacka, Amanda; Łoszakiewicz, Marta (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: Ovarian clear cell carcinoma is a rare type of ovarian cancer. In recent years, issues of the common genetic origin of endometriosis and ovarian clear cell carcinoma have been raised. Aim of this study was to evaluate the prevalence of this type of cancer, risk factors, prognosis and its potential aetiological association with endometriosis. Material and methods: In a retrospective study, we analysed histopathological data of patients operated in the First Department of Gynaecology and Obstetrics (MU, Lodz) due to ovarian cancer in 2004-2014. Among the 394 patients operated on for ovarian cancer, clear cell carcinoma was found in 0.02% (9/394). Menstrual history, parity, comorbidities, data from physical examination, operational protocols and histopathological diagnoses were analysed. Follow-up was obtained from 77.8% of patients. Statistical analysis was performed using Microsoft Excel 2013. Results: The mean age of patients at diagnosis was 57.6 years; the BMI in the study group was 27.2; the majority of patients were multiparous (77.8%). Clear cell carcinoma was detected mostly at stage Ia (n = 4). The concentration of Ca125 in the study group had an average of 142.75 U/ml and a median of 69.3 U/ml. The coexistence of endometriosis could not be clinically or histologically confirmed amongst our patients. The most common comorbidity in the study group was hypertension. Conclusions : In our clinical material, ovarian clear cell carcinoma is a rare histopathological specimen with a prognostic value comparable to that of serous ovarian cancer. Due to the rarity of this histopathological subtype, proving a cause-and-effect relationship between it and endometriosis can only be elucidated through statistical studies of the entire population.